Provisions for annulment in a reconciliation contract : A Comparative Study - Ibrahim, Hana; Abdul Reda, Hussein (Journal of Legal Sciences, 2023)
First of all, The annulment raises scientific and practical problems that reflect its peculiarity, as it relates to how the judge faces the dispute in a case in which reconciliation between the litigants took place, and what can be attributed to the judge’s judgment in this regard, whether that estimate is related to the factual elements in the case or the objective elements and their approach With the circumstances surrounding the dispute, and considering the possibility of applying the provisions of annulment established in the general rules, which is not easy in all cases due to the special nature of annulment in the conciliation contract, it is necessary to clarify the role that the judge plays, and his use of his legal tools that establish his authority and authority in Settlement of the dispute, in exchange for the right of the litigants to direct the litigation in the direction they see fit to settle the dispute by agreement between them through a reconciliation contract or resort to annulment in the event that one of them breaches the obligations imposed on him under the reconciliation contract.